Students’ perceptions of Education for Sustainable Development (ESD) to Achieve SDG 4 in Indonesia: a case study of Universitas Islam Riau - Titisari, Prima Wahyu; Elfis, Elfis; Zen, Irina Safitri; Hendrayani, Yani; Chahyana, Indry; ., Khairani; Janna, Nadiatul; Suharni, Nunut; Sari, Tika Permata (Springer Link, 2020)
Sustainable development at higher education level plays an important role in achieving the Sustainable Development Goals (SDGs). Higher education holds a great responsibility to increase the awareness and knowledge of students who will manage and develop resources. For the purpose of the sustainability of resources, awareness and knowledge of sustainable development are needed. This knowledge can be conveyed through Education for Sustainable Development (ESD) to achieve high education quality and equal access to education for women and men. Perception ofESDmust be studied to gather information about the facts, problems and challenges faced by Universitas Islam Riau (UIR) to achieve SDGs, especially SDG 4 (Quality Education). This study aims to identify the perception students of both genders at Universitas Islam Riau (UIR) hold about Education for Sustainable Development (ESD). This research is a descriptive survey research conducted using a quantitative approach. There were 99 respondents in this study, Consisting of 43 men and 56 women. Data was collected by distributing questionnaires containing 70 statements, while processing of questionnaire data was done through the frequency analysis formula. Generally, the results of social, environmental and economic aspects in the ‘Good’ category are between 71.08 and 78.75%. Based on gender, both female and male students scored a higher percentage in economic aspect than other aspects, whereby female students scored 77.76%, whereas it was 76.50% for male students. Based on this study, it can be concluded that the students of Universitas Islam Riau have a good perception of Education for Sustainable Development. Therefore, the University must begin to apply the concept of sustainable development in every aspect in order to contribute to achieving SDG 4.